Relationship of polycyclic aromatic hydrocarbons (PaHs) from vehicle emission in air particulate and plant leaves From highway roadsides in Johor, Malaysia - Azliyana Azhari,; Mohd Noh Dalimin,; Seow, Ta Wee (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Polycyclic aromatic hydrocarbons (PAHs) produced from the incomplete combustion of the organic and fossil fuel, and are usually attached to the particulate matter from the emission. Abundance of PAHs occurrence in the atmosphere has the ability to accumulate into vegetation. This study, by using selected species of plants is carried out to determine the relationship between the composition of PAHs in plants and the degree of PAHs pollution in the atmosphere to discover the ability of plants to absorb PAHs from the atmosphere. The study is concentrated on 3 toll station along PLUS’ North- South Expressway in Johor. From this study, it was observed that some plants are suitable for absorption of PAHs pollutant from the environment and suitable to be introduced as a medium for biomonitoring.